PREDICTORS AND OUTCOMES OF BIOLOGIC/IMMUNOSUPPRESSIVE THERAPY FOR PSC-ASSOCIATED IBD. (22nd January 2022) - Sayed, Amr; Silveira, Marina; Assis, David; Deng, Yanhong; Gaidos, Jill; Proctor, Deborah; Al-Bawardy, Badr
Abstract: BACKGROUND: Inflammatory bowel disease (IBD) coexists in up to 80% of patients with primary sclerosing cholangitis (PSC). PSC-IBD tends to be mild and responsive to mesalamine in most patients. However, some may require immunosuppressive (IMM) or biologic therapy to treat PSC-IBD. The aims of this study are to investigate the rates, predictors, and outcomes of biologic/IMM treatment of PSC-IBD. METHODS: This was a single center, retrospective study of patients with PSC from 1/1/2012 to 4/1/2021. Adult patients (age ≥ 18 years) with PSC-IBD were included. Primary outcomes were rates and predictors of biologic/IMM therapy to treat PSC-IBD. Secondary outcomes included rates of cholangitis, PSC-IBD clinical remission (per physician global assessment), endoscopic healing (absence of ulcers/erosions) in patients who required biologics/IMM. Patients who required biologics or IMM to treat PSC-IBD (biologic/IMM group) were compared to patients who did not require biologics/IMM. Continuous variables were compared using an unpaired Student's t-test. Categorical variables were compared using a Chi-square or Fisher's Exact test as appropriate. RESULTS: A total of 106 patients with PSC were reviewed and 72 (68%) had confirmed PSC-IBD and were included in the study. The median age was 48 years (IQR 33-59.5) and 69.4% were male (Table 1). A total of 22 patients (30.6%) required biologic/small molecule therapy (infliximab in 6; ustekinumab in 6; vedolizumab in 5; adalimumab in 4; tofacitinib in 1) and 6 (8.3%) needed thiopurine monotherapy to treat PSC-IBD. Overall, 28 patients (38.9%) required biologics/IMM to treat PSC-IBD. In the biologics/IMM group, 9 patients (32.1%) had small bowel involvement compared to 2 patients (4.6%) who did not require biologic/IMM (p=0.002). In the biologic/IMM group, 7 (25%) had overlap autoimmune hepatitis (AIH) compared to 3 (6.8%) in patients who did not require biologic/IMM for PSC-IBD (p=0.04). In the biologic/IMM group, 18 (64.3%) subjects were also treated with ursodeoxycholic acid (UDCA) compared to 29 (65.9%) in the non-biologic/IMM group (p=0.89). At least 1 episode of cholangitis was noted in 12 patients (42.9%) in the biologic/IMM group compared to 14 (31.8%) in the non-biologic/IMM group (p=0.34). In the biologic/IMM group, clinical remission was achieved in 22 patients (78.6%) but endoscopic healing in only 14 (50%). CONCLUSIONS: In our cohort, up to a third of patients with PSC-IBD required biologics/IMM. Small bowel involvement was associated with the need for biologic/IMM. The use of biologic/IMM resulted in clinical remission in over three quarters of the PSC-IBD subjects however endoscopic healing was only achieved in half. The use of biologics/IMM was not associated with a higher rate of cholangitis but larger studies are needed to investigate the effects of different biologic classes on outcomes.